Lugares, tempos e saberes em história da educação nas instituições de formação de professores no Brasil - Décio Gatti (EccoS – Revista Científica)
This paper relates results of a study which analyzes conceptions of education, training, institutions, and school disciplines present in the texts of Brazilian and foreign authors recognized in the field of History of Education; it distinguishes institutionalized aspects and organizational elements of the school which allow understanding of the principal categories of analysis present in contemporary historical educational investigations of school institutions. These preliminary theoretical methodological considerations assist in the analysis of the process of the establishment and transformation of Brazilian educational institutions dedicated to teacher training at primary, secondary and higher educational levels, during the 19th and 20th Centuries. This analysis is by means of an examination of the basic history, the organizational legislation, and the knowledge these institutions disseminated, particularly through the analysis of the itinerary that the discipline History of Education passed through in these teacher training courses offered in Brazil in the period in question.